2000
DOI: 10.1182/blood.v96.12.3719
|View full text |Cite
|
Sign up to set email alerts
|

An open-label study of the role of adjuvant hemostatic support with protein C replacement therapy in purpura fulminans–associated meningococcemia

Abstract: Activated protein C (APC) is a natural anticoagulant that plays a pivotal role in coagulation homeostasis. Severe inherited or acquired deficiency results in a clinical syndrome called purpura fulminans. In addition, APC also appears to have potent cytokine-modifying properties and is protective in animal models of sepsis. The dual functional properties of APC are particularly relevant to severe meningococcemia, where acquired PC deficiency is accompanied by multiorgan failure and purpura fulminans. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(61 citation statements)
references
References 43 publications
2
58
0
1
Order By: Relevance
“…Our observations concerning the reversal of DIC are in accordance with previously published case series [12–21]. Few studies have reported on the pharmacokinetics of protein C in patients with purpura fulminans and overt DIC.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our observations concerning the reversal of DIC are in accordance with previously published case series [12–21]. Few studies have reported on the pharmacokinetics of protein C in patients with purpura fulminans and overt DIC.…”
Section: Discussionsupporting
confidence: 92%
“…White et al . [20] conducted an open‐label study treating 36 patients with purpura fulminans and meningococcemia with a protein C zymogen concentrate. They found a mortality rate of only 8%, while the Glasgow Meningococcal Septicemia Prognostic Score (GMSP) [30] predicted a mortality rate of 50%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously shown in septic patients with DIC and in patients with overt DIC that lowered antithrombin and protein C, respectively, associate with increased mortality. To our knowledge, however, in the much larger group of acutely ill patients initially suspected of DIC that never actually develop DIC, it has not been previously shown that lowered antithrombin and especially lowered protein C allows identification of many more patients who are at a high risk of death and would not be identified using the overt DIC criteria alone.…”
Section: Discussionmentioning
confidence: 99%